2015
DOI: 10.1136/jnnp-2014-309828
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous mutation ofVWA3Bcauses cerebellar ataxia with intellectual disability

Abstract: Mutated VWA3B was found to be likely associated with cerebellar degeneration with intellectual disability. Although a rare cause of cerebellar degeneration, these findings indicate a critical role for VWA3B in the apoptosis pathway in neuronal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This site is located in the intron regions of VWA3B, which showed a tendency toward malignancy development. VWA3B encodes an intracellular protein thought to function in transcription, DNA repair, and membrane transport (Kawarai et al, 2016;Huttlin et al, 2017), playing a role similar to MACROD2, which was reported to influence DNA repair and sensitivity to DNA damage and result in chromosome instability (Sakthianandeswaren et al, 2018). In the patients of bladder urothelial carcinoma, evident copy number alterations were observed in the 2q12 regions in which the VWA3B was mapped (E. Pontes et al, 2013), in line with the suggestion that VWA3B plays a crucial role in bladder carcinogenesis.…”
Section: Rules For Homozygous Deletionsupporting
confidence: 65%
“…This site is located in the intron regions of VWA3B, which showed a tendency toward malignancy development. VWA3B encodes an intracellular protein thought to function in transcription, DNA repair, and membrane transport (Kawarai et al, 2016;Huttlin et al, 2017), playing a role similar to MACROD2, which was reported to influence DNA repair and sensitivity to DNA damage and result in chromosome instability (Sakthianandeswaren et al, 2018). In the patients of bladder urothelial carcinoma, evident copy number alterations were observed in the 2q12 regions in which the VWA3B was mapped (E. Pontes et al, 2013), in line with the suggestion that VWA3B plays a crucial role in bladder carcinogenesis.…”
Section: Rules For Homozygous Deletionsupporting
confidence: 65%
“…LPL , lipoprotein lipase, is increased in AD brains and associated with AD progression 33 . Mutations in VWA3B cause a recessive form of Spinocerebellar Ataxia 34 .…”
Section: Resultsmentioning
confidence: 99%
“…29 Only one pathogenic mutation in a case study has been reported in a similar protein, VWA3B, which, as homozygous, causes cerebellar ataxia. 30 The 3A domain is involved specifically in collagen binding, and this domain plays a key role in platelet adhesion in damaged blood vessels. Binding to collagen (specifically types I and III) via the 3A domain, which comes from the connective tissue of the vessel wall, allows the platelet plug to start formation.…”
Section: Discussionmentioning
confidence: 99%